Sexual differentiation of malaria parasites is controlled by unique epigenomic and proteomic cascades as revealed by comparative functional genome analyses - Birkholtz, Lyn-Marie (University of Pretoria, 2018)
Thesis (PhD)--University of Pretoria, 2017.